2022
DOI: 10.1186/s43046-022-00146-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of prognostic factors in patients with brain metastases affecting survival

Abstract: Introduction Brain metastases (BM) are associated with dismal prognosis as they cause significant morbidity and affect the quality of life of patients. Management of BM depends on the following factors: age, patient performance, size and the number of lesions, location of the tumor, comorbidities, primary tumor type, and extracranial disease burden. In the present study, the pattern of occurrence, clinical characteristics, treatment outcome of brain metastases, and factors, tumor characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This result was supported by the Kaplan-Meier curves (Figure 1). The results of a study by Gupta et al 14 in which 70% of the patients had lung cancer showed that female sex was a factor affecting the overall survival of patients with BM. Patients with NSCLC that led to the development of BM had a higher frequency of EGFR mutations than patients without BM; conversely, among patients with NSCLC and EGFR mutations, the incidence of BM (70%) was higher than that in patients with NSCLC and wild-type EGFR (38%).…”
Section: Discussionmentioning
confidence: 99%
“…This result was supported by the Kaplan-Meier curves (Figure 1). The results of a study by Gupta et al 14 in which 70% of the patients had lung cancer showed that female sex was a factor affecting the overall survival of patients with BM. Patients with NSCLC that led to the development of BM had a higher frequency of EGFR mutations than patients without BM; conversely, among patients with NSCLC and EGFR mutations, the incidence of BM (70%) was higher than that in patients with NSCLC and wild-type EGFR (38%).…”
Section: Discussionmentioning
confidence: 99%
“…Podophyllotoxin, its derivatives and analogues finds a lot of scopes in pharmaceutical field as it show wide biological activities. Several researchres worked on the analogues of podophyllotoxin and its derivatives for variety of biological activities such as cathartic, cytotoxic, antimitotic, anticancer, antitropical skin disease, antimalarial, virucidal, fungicidal [5][6][7][8][9][10][11][12][13][14][15][16][17][18] . In the present work the analogues of podophyllotoxin 6, 6adihydro-2, 3-dimethoxy-9-methyl-11bH benzo [c] fluoren -5, 7 dione and 6, 6a-dihydro-3-methoxy-2, 9-dimethyl-11bH benzo [c] fluoren -5, 7 dione.…”
Section: Discussionmentioning
confidence: 99%
“…The sandoz company in Basel (Switzerland) have developed a number of semi synthetic derivatives mainly glycosides that have retained the desirable antimitotic activity and lost the undesired side effects. At least four of these VIZ: SP-1 and SP-G, VM-26 (tenoposide) and VP-16-213 (etoposide) are now in clinical use [14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…We observed that patients with adenocarcinoma generally have a longer OS compared to other types, while those with tumors that are di cult to accurately categorize under the microscope have the poorest prognosis. One year ago, in a study on BMs conducted by Gupta, it was similarly observed that patients aged 41-50 years and with an adenocarcinoma histological subtype experienced a longer survival period [12]. GPA, as a commonly used scoring system for assessing the prognosis of intracranial tumor patients, is primarily employed to predict the survival period of these patients.…”
Section: Predictive Modelmentioning
confidence: 99%